2018
DOI: 10.7752/jpes.2018.04371
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of the present study was to compare the load influence on the time under tension (TUT), electromyographic activity (EMG) and blood lactate concentration (LAC) in 8, 10, and 12RM and the relationship between the TUT and the number of repetitions in the squat exercise. The sample consisted of ten military men (age: 18.90 ± 0.32 years, height: 1.73 ± 0.05 m, body mass: 67.55 ± 4.96 kg, body fat: 6.54 ± 1.87%). The TUT for 8, 10, and 12RM was verified by kinematic using the timing technique of the Kino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 28 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…However, general muscle myoelectric activities amplified with increasing loads, but significant increases in EMG signals were observed only in the vastus medialis (VM) and gluteus maximus (GM) muscles with 90% and 100% of 1RM loads. Likewise, Silva et al [18] when submitted the sample to the squat exercise, observed an increase in the EMG activity of the GM and VM with increasing loads of 60% to 90% of 1RM.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…However, general muscle myoelectric activities amplified with increasing loads, but significant increases in EMG signals were observed only in the vastus medialis (VM) and gluteus maximus (GM) muscles with 90% and 100% of 1RM loads. Likewise, Silva et al [18] when submitted the sample to the squat exercise, observed an increase in the EMG activity of the GM and VM with increasing loads of 60% to 90% of 1RM.…”
Section: Discussionmentioning
confidence: 83%
“…The purpose of this systematic review was to describe the effects of the back squat exercise on the lower limb myoelectric activity in trained men. The analysis of the eight cross-sectional studies [12][13][14][15][16][17][18][19] showed greater muscle myoelectric activity during different squat protocols, but these do not represent a greater strength gain promoted by the type of exercise (p < 0.05).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations